2017
DOI: 10.15406/apar.2017.06.00231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mycorrhizal Fungi Inoculation on Green Pepper Yield and Mineral Uptake under Irrigation with Saline Water

Abstract: High salinity in soil or irrigation water has detrimental effects on plant nutrition and reduces crop growth and yield. In this study, the effects of pre-inoculation of green pepper (Capsicum annuum L., cv. Zingaro) with arbuscular mycorrhizal (AM) fungi on mineral uptake, growth and fruit yield under irrigation with saline water were investigated. Pepper seedlings were transplanted into nonsterile soil plots under polyethylene covered plastic house conditions and irrigated with saline water of three levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Fe metabolism is of importance in nodules since this metal is a constituent of key proteins such as nitrogenase and leghemoglobin (Moreau et al, 1995). The increments in plant growth parameters due to application of inoculum with AMF might be attributed to the enhancing of nutrients uptake, increment in nitrogen fixation, phosphate solubilization and synthesis of phytohormones as reported by previous research work (Al-Karaki 2017;Sathiyadash et al 2017;Pereira et al, 2019). These results might be due to Fe roles in contributing to other nutrients in increasing plant growth.…”
Section: Disussionsupporting
confidence: 64%
“…Fe metabolism is of importance in nodules since this metal is a constituent of key proteins such as nitrogenase and leghemoglobin (Moreau et al, 1995). The increments in plant growth parameters due to application of inoculum with AMF might be attributed to the enhancing of nutrients uptake, increment in nitrogen fixation, phosphate solubilization and synthesis of phytohormones as reported by previous research work (Al-Karaki 2017;Sathiyadash et al 2017;Pereira et al, 2019). These results might be due to Fe roles in contributing to other nutrients in increasing plant growth.…”
Section: Disussionsupporting
confidence: 64%
“…Significant growth promotion effects of AM fungi, i.e., enhanced growth of seedlings in nurseries and improved performance after planting in the field [13,14] improved stand establishment rate and enhanced plant resistance to soil salinity immediately after transplanting [15,16], and increased root and shoot dry matter [14], are reported in various vegetable crops. Similarly, growth-promoting capabilities of bacteria such as; nitrogen fixation, phosphate solubilization, iron sequestration, synthesis of phytohormones, modulation of plant ethylene levels ( [17,18] are also largely documented.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previously reported increased beneficial aspects of the association of mycorrhizae fungi and Rhizobium sp., with pulse crops [40], we found that combined application of AM fungi (Rhizophagus irregularis + Claroideoglomus claroideum) and N-fixing bacteria (Rhizobium leguminosarum) were able to maintain average grain weight at the level of non-saline plants and having significantly higher yield than control plants. Improved plant nutrition due to the presence of AM fungi [14,41] and facilitation of the acquisition of nutrient resources or the alteration of plant hormone levels by root-colonizing bacteria [30,42,43], should be the reasons for better vegetation and highest yield in dually inoculated plants. Even though it was significantly less than AMF + Rh.l variant, the AMF + Brh combination and single application of Rhizophagus irregularis and Burkholderia were capable of providing significantly higher yields than the control plants.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic behavior of bio-inoculants and R. intraradices was also corroborated by maximum increase in TKN and AVP level of treatments BMRIV, RIV, PMRIV and ACRIV (bio- (Table 1). Congruent to this study, Al-Karaki [42], showed that AM fungi had a positive influence on the composition of mineral nutrients (particularly immobilized nutrients such as P) of plants under salt stress conditions.…”
Section: Effect On Physico-chemical Properties Of Postharvest Soilmentioning
confidence: 54%